Night-Time Non-dipping Blood Pressure and Heart Rate: An Association With the Risk of Silent Small Vessel Disease in Patients Presenting With Acute Ischemic Stroke - Akhtar, Naveed; Al-Jerdi, Salman; Kamran, Saadat; Singh, Rajvir; Babu, Blessy; Abdelmoneim, Mohamed S.; Morgan, Deborah; Joseph, Sujatha; Francis, Reny; Shuaib, Ashfaq (Frontiers in Neurology, 2021)
Background and purpose: Nocturnal non-dipping blood pressure and heart rate are associated with an increased risk of cardiovascular disease. The effects of such variance on cerebrovascular disease have not been well studied. Methods: The 24-hour ambulatory blood pressure (ABPM) and heart rate were monitored with B-pro in patients with acute stroke within the initial week of hospital admission. The risk factor profiles, clinical presentation, imaging, and short-term prognosis were compared in nocturnal dippers and non-dippers (more than 10% nocturnal decrease) of blood pressure and heart rate. Results: We enrolled 234 patients in whom ABPM and MRI data were available. Heart rate data were available in 180 patients. Lacunar sub-cortical stroke was the most common acute lesion (58.9%), while hypertension (74%) and diabetes (41.5%) were the most common associated risk factors. ABPM revealed non-dipping in 69% of patients. On univariate analysis, Small Vessel Disease (SVD) was significantly more frequent in non-dippers vs dippers (BP: 56.8% vs 40.3% p=0.02; heart rate: 57.9% vs 40.7% p 0.03). Silent strokes were also more frequent in non-dippers vs dippers (BP: 40.7% vs 26.4% p=0.35; heart rate: 44.6% vs 25.4% p=0.01). Multivariate analysis revealed SVD to be significantly related to age, hypertension, blood pressure non-dipping, and severity of symptoms at index event. Conclusions: The presence of nocturnal non-dipping of blood pressure and heart rate are associated with an increased risk of silent stroke and SVD. Increased use of ABPM may allow for improved diagnosis of non-dippers